KAJIAN ONTOLOGI, EPISTIMOLOGI, DAN AKSIOLOGI DALAM FILSAFAT HUKUM - Halim, Abdul; Maryani, Halimatul; Zikrillah, Ridho (Asosiasi Pengajar Hukum Tata Negara dan Hukum Administrasi Negara (APHTN-HAN) Sumatera Utara, 2022)
The philosophy of law is part of general philosophy, as it offers philosophical reflection on the foundation of law itself. The object of legal philosophy is in the law itself. The law is closely related to the norms that govern human behavior. The philosophy of law is the first step to the end of the excavation of the pearl of law, menelistic to the bottom of the problem causing how one action and event will be governed by law. As a substance in the concept of legal philosophy it is very closely related to Ontology, Epistimology, and Axiology. In this study, the analysis of exposure is to use normative studies using qualitative analysis.